2006
DOI: 10.1037/0021-843x.115.1.166
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for a causal relationship between smoking lapse and relapse.

Abstract: In this study, the authors prospectively evaluated the impact of a smoking lapse on relapse probability. After 4 days of smoking abstinence, 60 smokers were randomly assigned to smoke 5 nicotine-containing or 5 denicotinized cigarettes, or to remain abstinent (no lapse) during a 4-hr time period. Afterward, smoking abstinence was encouraged with monetary incentives, and smoking behavior was tracked for 6 days. Relative to the no-lapse condition, exposure to either of the cigarette types more than doubled the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 40 publications
3
76
0
Order By: Relevance
“…Any effect that the lapse sessions may have had on the likelihood of smoking cannot be determined in the present study due to the absence of a 14C condition with participants who did not attend lapse sessions. Indeed, in one of the two studies of which we are aware that showed an increase in relapse risk associated with exposure to programmed lapses (five cigarettes in 4 hr), denicotinized cigarettes were just as effective at increasing the likelihood of smoking as standard cigarettes (Juliano, Donny, Houtsmuller, & Stitzer, 2006). The failure to find differences between nicotinized and denicotinized cigarettes suggests strongly that the stimulus factors of smoking (e.g., sight and feel of cigarette, smell and taste of smoke) are important to any effect of programmed lapses on the probability of future smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Any effect that the lapse sessions may have had on the likelihood of smoking cannot be determined in the present study due to the absence of a 14C condition with participants who did not attend lapse sessions. Indeed, in one of the two studies of which we are aware that showed an increase in relapse risk associated with exposure to programmed lapses (five cigarettes in 4 hr), denicotinized cigarettes were just as effective at increasing the likelihood of smoking as standard cigarettes (Juliano, Donny, Houtsmuller, & Stitzer, 2006). The failure to find differences between nicotinized and denicotinized cigarettes suggests strongly that the stimulus factors of smoking (e.g., sight and feel of cigarette, smell and taste of smoke) are important to any effect of programmed lapses on the probability of future smoking.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nicotine patch did not signifi cantly reduce total withdrawal, consistent with other studies of briefl y abstinent smokers not trying to quit permanently ( Teneggi et al, 2002 ; see also Perkins, Stitzer, & Lerman, 2006 ) but contrary to most clinical trial results ( Jorenby, Keehn, & Fiore, 1995 ). Moreover, analyses of abstinence effects by time of day were limited to the participants who self-selected to abstinence during the patch weeks, as with all cessation studies, including all outpatient and some inpatient studies of enforced abstinence (since not all are able to abstain even when paid to do so; e.g., Juliano, Donny, Houtsmuller, & Stitzer, 2006 ). Yet the time-of-day effects were strongest while participants were smoking, suggesting good generalizability of our fi ndings regarding the main effects of time of day to symptom levels in the general population of smokers while they smoke (see Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…At 16:00, following approximately 24 hr of abstinence (overnight included), participants smoked two cigarettes of their preferred brand spaced 45 min apart in an experimental simulation of lapse exposure. Following each lapse cigarette, participants completed a 19-item Cigarette Rating Questionnaire (based on Juliano, Donny, et al, 2006 ), in which they rated their experience of the lapse cigarette on a 100 point visual analog scale anchored on the left with not at all and on the right with extremely. The items to be rated fell into four categories: (a ) rewarding and/or enjoyable effects of smoking (pleasant, tasted good, satisfying, relaxing, made me feel buzzed, liked effect, and stimulating), (b ) physical sensations from smoking (enjoyable sensations in the throat and chest, enjoyable sensations on the lips and tongue, and smelled good), (c ) removal of aversive stimuli (reduced craving, reduced withdrawal, and reduced irritability), and (d ) unpleasant and/or punishing responses to smoking (harsh, strong, tasted different than usual brand, intensity, made me feel dizzy, and made me feel nauseous).…”
Section: Nicotine and Tobacco Researchmentioning
confidence: 99%
“…A model of smoking cessation and relapse has been developed in which a brief period of objectively verifi ed abstinence is followed by a programmed smoking lapse in a laboratory setting ( Chornock, Stitzer, Gross, & Leischow, 1992 ;Juliano, Donny, Houtsmuller, & Stitzer, 2006 ). In this model, all participants experience the smoking lapse, and subjective ratings of the cigarette(s) can be immediately completed.…”
Section: Effects Of Varenicline On Abstinence and Smoking Rewardmentioning
confidence: 99%
See 1 more Smart Citation